2019
DOI: 10.1002/ange.201910060
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Nanoparticle Catalysis with Organogermanes

Abstract: Although nanoparticles are widely used as catalysts, little is knownabout their potential ability to trigger privileged transformations as compared to homogeneous molecular or bulk heterogeneous catalysts.W eh erein demonstrate (and rationalize) that nanoparticles displayorthogonal reactivity to molecular catalysts in the cross-coupling of aryl halides with aryl germanes.W hile the aryl germanes are unreactive in L n Pd 0 /L n Pd II catalysis and allowselective functionalization of established coupling partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 37 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…Despite enormous success in this area, the need for more rapid, selective, advanced synthetic methodologies drives search for new coupling partners. Recently, organogermanes [1][2][3][4][5] have emerged as perspective coupling partners to circumvent limitations of traditional organozinc and organomagnesium reagents 6,7 (low functional group tolerance); organosilanes 8 (low reactivity), organostannanes [9][10][11] (acute toxicity: endocrine disruptors, immunotoxicants, carcinogens and obesogens); and organoboronic acids 12,13 (acid/base sensitivity). In this regard, vinylgermanes are of particular interest as versatile synthetic building blocks due to their low toxicity, 14 resistance to protonolysis, 15 and benchtop stability.…”
mentioning
confidence: 99%
“…Despite enormous success in this area, the need for more rapid, selective, advanced synthetic methodologies drives search for new coupling partners. Recently, organogermanes [1][2][3][4][5] have emerged as perspective coupling partners to circumvent limitations of traditional organozinc and organomagnesium reagents 6,7 (low functional group tolerance); organosilanes 8 (low reactivity), organostannanes [9][10][11] (acute toxicity: endocrine disruptors, immunotoxicants, carcinogens and obesogens); and organoboronic acids 12,13 (acid/base sensitivity). In this regard, vinylgermanes are of particular interest as versatile synthetic building blocks due to their low toxicity, 14 resistance to protonolysis, 15 and benchtop stability.…”
mentioning
confidence: 99%
“…However, compared with other metal-or metalloid-containing heterocyclic nucleophilic reagents, rather less attention has been paid to Ge-containing heterocyclic nucleophiles, since Ge-related cross-coupling reactions were scarcely reported. [6] Our group has been focusing on developing a series of facilely synthesized, air-and moisture-stable and environmental-friendly germatranes (abbreviated as Ge in following text) as nucleophiles for Pd-catalyzed crosscoupling reaction. [7] Our previous studies have revealed that germatranization of heterocyclic halides could furnish various Ge-containing heterocyclic nucleophiles (Scheme 1a), [7a] which were also proved to be competent for construction of complex heterocycles under Pd-catalyzed cross-coupling reaction conditions.…”
mentioning
confidence: 99%
“…Recently, our group added organogermanes (-GeR 3 ) [5] to the selectivity toolbox, which are robust, non-toxic, easily installable, [6] and unreactive in standard Pd 0 /Pd II -catalyzed couplings, while privileged coupling partners with aryl iodides under nanoparticle catalysis that outcompete for example, ArBPin or ArBMIDA. [7] However, the currently available sequential or iterative coupling repertoire with Pd is far from complete, and the increasing demands towards a rapid and automated exploration of chemical space will greatly benefit from new and orthogonal disconnections. [8] For example, none of these methods allow to assemble richly decorated small molecules in the presence of CÀiodine bonds, which owing to their pronounced halogen bonding [9] are receiving increasing interest in medicinal and materials chemistry.…”
mentioning
confidence: 99%
“…We subsequently explored the scope of the couplings and investigated especially those aryl germanes that would, as the corresponding aryl boronic acids, be unstable and sluggishly reactive or incompatible in the widely employed Pd-catalyzed Suzuki cross coupling, [21] that is, highly fluorinated, heterocyclic, sterically hindered as well as halogenated aryl germanes. [7] The presence of fluorine in ortho-or para-positions of the germane (1-3, see Table 1) as well as electron-rich heterocycles, such as the sterically demanding isoxazole (16), 2-and 3-substituted thiophenes (15,17), and a 1,3-benzodioxole (18) were well tolerated. Notably, analogous couplings of the latter previously needed metal and base additives to proceed.…”
mentioning
confidence: 99%
See 1 more Smart Citation